Unveiling Students’ Perceptions on Metacognitive Dimensions in Reading Comprehension at an Islamic University - Adisaturrahimi, Andi; Dollah, Syarifuddin; Halim, Abdul; Hasanah, Uswatun; Setiadi, Muhammad Astrianto (Universitas Negeri Makassar, 2024)
This study explored the perceptions of 18 students from IAIN Bone through a series of structured interviews. Using the qualitative method, the results indicated that most students had a positive perception of metacognitive dimensions, particularly appreciating how these strategies enhance comprehension, promote active participation, and foster classroom interaction. Three main themes were found: emotional engagement with the learning process, affective engagement and emotional support, and experiential learning process. However, some students expressed challenges, including feelings of nervousness and anxiety related to the frequent questioning and active engagement required. Despite these challenges, most students strongly desired to continue using metacognitive dimensions in future classes. These findings suggested that while metacognitive dimensions are generally well-received, their implementation required sensitivity to students' varying levels of comfort with active participation. This study enhanced the comprehension of student perceptions and provided insights for lecturers aiming to incorporate metacognitive approaches into reading comprehension classes